Short-term effects of fire on small rodents in the Brazilian Cerrado and their relation with feeding habits - Vieira, Emerson M.; Briani, Denis C. [UNESP] (CSIRO Publishing, 2013)
We investigated the short-term (up to 60 days) fire effects on small rodents and their relation to feeding habitats in the fire-prone Cerrado of central Brazil, the most species-rich savanna in the world. We conducted prescribed-fire experiments with pre- and post-fire simultaneous sampling in burned and unburned areas to investigate the hypothesis that the effects of fire on the abundance of small rodents is related to changes in food availability and consequently the feeding habits of the animals. The findings revealed a higher availability of invertebrates in just-burned areas compared with plant resources. Stomach analyses indicated that invertebrate consumption increased after fire for the four most common rodents, but Calomys tener and especially Calomys expulsus, consumed more invertebrates in the burned areas than Necromys lasiurus or Cerradomys scotti. These Calomys rodents were also the post-fire dominant species. Thus, even within the group of rodents that are generalist feeders, distinctive short-term responses to fire were associated with changes in resource availability and with resultant differences in the abundance of plant matter and invertebrates in the rodent diets.
Keywords: Brazil; Calomys; Cerradomys; Necromys; small mammals